A case study of digitization programs in academic libraries in the National Capital Region (NCR) - Lagas, Sammy S. II
Despite increasing demand for more convenient and more accessible forms of information, many academic institutions’ digital collections are still severely lacking. This is due to the absence of a digitization program within said institutions. Contributory to this is the luck of funding, technical expertise, and physical and social resources necessary to implement a digitization program in-house. In order to circumvent these issues, some institutions outsource their digitization activities to digitization service providers. Doing so allows them to continually address client needs without going over budget. The study aims to document the narratives and rationales behind the digitization programs of academic libraries in the National Capital Region so as to provide more insight in their management and implementation.